How Dispositional Gratitude Shapes Employee Well-being and Organizational Commitment: The Mediating Roles of Leader-Member Exchange and Coworker Exchange. (February 2023) - Zhao, Teng; Li, Hairong; Zheng, Lu; Zhang, Yuyan
Dispositional gratitude has recently emerged as a variable of interest in organizational contexts. However, it remains unclear whether dispositional gratitude is predictive of employee well-being, with limited theoretical and empirical elucidation of the underlying mechanisms. To address these limitations, the present study investigated dispositional gratitude as a predictor of employee well-being and organizational commitment. Drawing on the broaden-and-build theory of positive affect, the study also examined whether the social bonding resources of leader-member exchange (LMX) and coworker exchange (CWX) mediated these effects. The participating employees ( N = 300) completed the survey in three waves at one-week intervals. The results of structural equation modeling (SEM) confirm that dispositional gratitude is positively related to employee well-being and organizational commitment and that these effects are mediated by LMX and CWX. The paper concludes by discussing the theoretical and practical implications of these findings, the study's limitations, and future research directions.